Queering Early Childhood Studies: Challenging the Discourse of Developmentally Appropriate Practice - Janmohamed, Zeenat (Alberta Journal of Educational Research, 2010)
This article reviews approaches to early childhood training and practice in Ontario and sets it in the wider context of feminist poststructural knowledge production. Through a feminist poststructural reading, this article uncovers dominant assumptions of universality underlying the heteronormative discourse of developmentally appropriate practice that dominates early childhood training, postsecondary program curriculum, and professional learning and practice. It argues that postsecondary studies in early childhood education must challenge the pervasive heteronormative discourse in order to shift early childhood practice toward a viewpoint that is counter-hegemonic and integrates queer perspectives.